Charting American Habitus: an analysis of ‘middlebrow’ fiction and its readership through the prism of Donna Tartt’s published novels - Beestone, Kelly (2018)
This thesis aims to address the paucity of research on contemporary middlebrow fiction and the ongoing tensions in the American literary hierarchy by focussing on the published novels of author Donna Tartt. By examining Tartt’s fiction both through a close reading analysis and an examination of paratextual elements of her work, this thesis argues that Tartt’s novels fall somewhere in the liminal space between highbrow and lowbrow culture. Each chapter looks at one of her novels in detail, drawing on Pierre Bourdieu’s theories on cultural capital and taste as a prism through which Tartt’s books might be examined. The introduction explores the history of literary tensions in America. The first chapter examines the role of protagonist Richard Papen in The Secret History and his position as an unreliable narrator. Chapter two looks at the merging of literary genres in The Little Friend, with a particular focus on the fusing of Southern Gothic and Sentimental fiction. Lastly, chapter three analyses the importance of art in The Goldfinch, concentrating on the Carel Fabritius painting for which Tartt’s novel is named. It is the intention of this thesis to show through each chapter that Tartt balances the cerebral with the emotional, and offers highbrow critics who dismiss her work as ‘popular’ a riposte by opening discussions about what constitutes taste in literature.